2008
DOI: 10.1063/1.2967479
|View full text |Cite
|
Sign up to set email alerts
|

Electrostatic drift waves in nonuniform quantum magnetized plasmas

Abstract: Electrostatic drift waves ͑EDWs͒ in nonuniform quantum magnetized plasmas are described by the quantum hydrodynamic model. Electrons are viewed as a low-temperature Fermi gas. Analytical expression of the dispersion relationship of the quantum EDW is presented. Quantum effects are shown to affect the dispersion of the EDW significantly. The effects on the dispersion relation due to the magnetic field and spatial inhomogeneity give rise to results similar to the classical case. Our results should be relevant to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 29 publications
0
15
0
Order By: Relevance
“…͑13͒ can be rewritten as v te , which is the quantum electron-acoustic speed. 62 respectively. We see that the first mode is the electronacoustic wave while the second mode is the Langmuir wave with quantum effect corrections in pair plasmas, in which the plasma frequency p is modified as p 2 =2 e 2 .…”
Section: ͑19͒mentioning
confidence: 95%
“…͑13͒ can be rewritten as v te , which is the quantum electron-acoustic speed. 62 respectively. We see that the first mode is the electronacoustic wave while the second mode is the Langmuir wave with quantum effect corrections in pair plasmas, in which the plasma frequency p is modified as p 2 =2 e 2 .…”
Section: ͑19͒mentioning
confidence: 95%
“…Shukla and Stenflo 23 found new drift modes in nonuniform quantum magnetoplasmas and observed that the Bohm potential term significantly modified the electron drift wave frequency. Wu et al 24 investigated the electrostatic drift vortices in quantum magnetoplasmas employing the QHD model and found that the waves got modified significantly by the quantum corrections. Masood et al 25 investigated quantum ion acoustic vortices in an inhomogeneous plasma and found that electrostatic monopolar, dipolar, and vortex street type solutions could appear in such a plasma.…”
Section: Introductionmentioning
confidence: 99%
“…Shukla and Stenflo 12 found new drift modes in nonuniform quantum magnetoplasmas and observed that the Bohm potential term significantly modified the electron drift wave frequency. Wu et al 13 studied the electrostatic drift vortices in quantum magnetoplasmas employing the QHD model and found that the waves got modified significantly by the quantum corrections. Masood et al 14 investigated quantum ion acoustic vortices in an inhomogeneous plasma and found that electrostatic monopolar, dipolar, and vortex street type solutions could appear in such a plasma.…”
Section: Introductionmentioning
confidence: 99%